The Effectiveness of an Early Rehabilitation Program Using Remote Technologies on an Outpatient Basis in Patients after Surgical Correction of Acquired Valvular Heart Defects - o'g'li, Naimov Dilshod Qayim (Journal of Science in Medicine and Life, 2024)
Purpose of the study: to study the clinical safety and effectiveness of combined rehabilitation, including early rehabilitation with physical training in the hospital and remote rehabilitation using a mobile application on an outpatient basis, in patients after correction of acquired valvular heart disease (AVH) under conditions of artificial circulation. Material and methods: The study included 68 patients who underwent surgical correction of PPS. Depending on the approach to rehabilitation, patients are divided into two groups: the main group (n=34) and the control group (n=34). In the main group, two subgroups of patients were identified depending on the rehabilitation performed: a subgroup of combined rehabilitation (n=16) with the inclusion of treadmill training at the early hospital stage, at least from the 8th day after surgery for 2 weeks. and remote rehabilitation at the outpatient stage using a mobile application, and a subgroup of remote rehabilitation (n=18) without the use of early treadmill training at the inpatient stage. In the control group, only standard methods of cardiac rehabilitation were used. Research results: No statistically significant differences were found in the frequency and nature of complications in the early postoperative period. A more pronounced positive dynamics of the functional status of patients from the combined rehabilitation subgroup was demonstrated 24 days after surgery in comparison with patients without the inclusion of early physical training in the rehabilitation program. In the subgroup of combined rehabilitation, there was a more significant increase in the indicators of exercise tolerance (p = 0.03) and peak oxygen consumption (p = 0.04) in dynamics 24 days after surgery with their further increase (p = 0.04; p =0.03) by the 4th month of observation compared with those on the 7th day of the postoperative period, when compared with the dynamics in the remote rehabilitation group. Among patients undergoing combined rehabilitation, there was a higher adherence to regular use of a mobile application for remote rehabilitation than among patients from the remote rehabilitation subgroup - 50% versus 38.8%, respectively (p = 0.04). Conclusion: a rehabilitation program for patients with PPS after surgical correction of the defect, including early moderate-intensity physical treadmill training followed by outpatient remote rehabilitation using a mobile application, demonstrates its safety and effectiveness in the form of a significant improvement in the patient’s functional status. At the same time, the early start of physical training is associated with increased adherence to the use of remote rehabilitation technologies in the future.